Visceral fat measured by computed tomography and the risk of breast cancer - Kim, Myeong Seong; Choi, Yoon-Jung; Lee, Yoon Hyeon (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: Obesity is a risk factor for the development of breast cancer, which can be examined to assess the association between abdominal fat distribution through computed tomography (CT) and risk of breast cancer by hormone receptor (HR) status in women. Methods: We examined 234 cases of newly diagnosed breast cancer patients and 211 controls consisting of health examinees in the Republic of Korea. The abdominal body fat distribution was measured by CT scan. The subjects’ medical information, obtained from electronic medical records (EMR), were analyzed to verify the association between visceral fat and the type of breast cancer by HRs. Results: While visceral obesity increased the risk of breast cancer in post-menopausal women by 1.50 (95% CI, 0.75–2.98), the effect was not observed in pre-menopausal women 0.86 (95% CI, 0.44–1.62). Also, histological grade was associated with visceral fat, which higher histological grade score (≥2) showed a slightly increased mortality rate (r=0.15, P=0.07). Patients with negative progesterone receptors tended to have a higher abdominal fat ratio than patients with positive progesterone receptors. Especially in pre-menopausal women, higher distribution of abdominal fat ratio in breast cancer patients had somewhat more of an effect on negative than positive HRs [estrogen receptor (ER), P=0.12; progesterone receptor (PR), P=0.06; human epidermal growth factor receptor 2 (HER2), P=0.43]. Conclusions: Our results suggest that the clear association between breast cancer and distribution of abdominal fat, and the abdominal fat ratio, are useful indicators for risk factors for breast cancer as well as malignancy.